A Dual-Adaptive Perspective on PV Array Reconfiguration with Genetic Algorithms Under Partial Shading Conditions - Karaduman, Ozgur; Parlak, Koray Sener (Mdpi, 2025)
Photovoltaic systems are among the most popular renewable energy sources due to their ease of installation and low operating costs. However, they are characterized by low efficiency, non-linear electrical properties, and sensitivity to radiant intensity on the panels. To address these limitations, researchers have focused on improving the efficiency of these systems. The most effective method for enhancing the maximum power point of a PV array is reconfiguration, which involves rearranging the connection structures of the panels. This study presents a method for determining the reconfiguration of panels based on their radiant intensity using a genetic algorithm (GA). The method matches the rows of the PV array to achieve similar radiant intensities, thereby increasing power efficiency. An algorithm was developed to enable the adaptive panels to connect to any row of the fixed section in a PV array divided into dual-adaptive and fixed sections, controlling this connection structure. This GA-based algorithm utilizes short-circuit currents obtained from specific points of the PV array to identify the most suitable connection structure within the solution space and generates control signals for reconfiguration. Simulation results with various array structures and shading scenarios demonstrate that the proposed method increases array efficiency and achieves results within a practically applicable cycle time.
Keywords: photovoltaic panel; PV array reconfiguration; partial shaded conditions; maximum power point; genetic algorithms; optimization